First Forum of China and the Community of Latin American and Caribbean States (CELAC): Exploring opportunities for cooperation on trade and investment - NU. CEPAL (ECLAC, 2015)
This document is a contribution by the United Nations Economic Commission for Latin America and the Caribbean (ECLAC) to the First Forum of China and Community of Latin American and Caribbean States (CELAC),(Beijing, 8 and 9 January 2015). The document consists of three parts. The first part summarizes the main components of the international economic scenario for Latin America and the Caribbean. The second part provides a brief overview of trade and investment relations between the region and China. And the third part sets out conclusions and recommendations for improving the quality of economic ties between the two trading partners..